KARAKTERISTIK INGOT PADUAN U-Zr-Nb PASCA PROSES QUENCHING - Masrukan; Setiawan, Jan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The U-Zr-Nb heat-quenching experiment has been subjected to various Nb compositions. Ingots of U-Zr-Nb alloys with varying Nb compositions are 1%, 4% and 7% and a fixed 10% Zr composition is made by melting U, Zr and Nb metals in an electric arc furnace. The quenching experiment is intended to convert an unstable phase αU into stable γU phase. Quenching experiment is intended to convert an unstable phase αU phase into a stable γU phase. In quenching experiments, the U-10Zr-1Nb, U-10Zr-4Nb, U-10Zr-7Nb ingot ingredients were fed into box that made of steel plate and then fed into a heating furnace and heated at 900 C and held for 2 hours for then cooled rapidly in water. After quenched then subjected to phase testing and microstructure observation. The phase test is performed using X-ray diffraction (XRD) and the data is processed using HighScore software, while the microstructure observation using optical microscope. Test results with XRD showed that the U-10Zr-1Nb alloy before quenched consisted only of an αU phase, the U-10Zr-4Nb alloy consist of 23,1504% αU phases and 76,8495% γU phases, while U-10Zr-7Nb consist of 34,1873% αU phases and 65,8127% γU phases. For U-10Zr-1Nb alloys after quenched consist of an αU phase, the U-10Zr-4Nb alloy consist of 44% αU phases and 46% γU phases, the U-10Zr-7Nb alloy consisted of 19% αU and 81% phases γU. For U-10Zr-1Nb alloys after quenched consist of an αU phase, the U-10Zr-4Nb alloy consisted of 44,6711% αU phases and 55,3289% γU phase, the U-10Zr-7Nb alloy consist of 17,9918% αU phases and of 82,0082% γU phases. The results of the theoretical density analysis on the phases formed on U-10Zr-1Nb, U-10Zr-4Nb, U-10Zr-7Nb alloys both before and after quenched were obtained that ingot of U-10Zr-1Nb, U-10Zr-4Nb alloy U-10Zr-7Nb shows that the αU and γU phase densities decrease slightly if the Nb content is lower. Meanwhile, microstructure observation results showed that in the higher of Zr content (7% Nb) will form smaller grains (fine) after quenching. It can be concluded that the quenching process of U-10Zr-1Nb, U-10Zr-4Nb and U-10Zr-7Nb alloys will change the phase that is from the αU phase to γU and the change the microstructure formed. The microstructural changes show that in the higher Nb content, the grains that are formed become finer.